Malaria vaccine candidates displayed on novel virus-like particles are immunogenic and induce transmission-blocking activity - Chan, Jo-Anne; Wetzel, David; Reiling, Linda; Miura, Kazutoyo; Drew, Damien R.; Gilson, Paul R.; Anderson, David A.; Richards, Jack S.; Long, Carole A.; Suckow, Manfred; Jenzelewski, Volker; Tsuboi, Takafumi; et al. (PLOS ONE, 2019)
The development of effective malaria vaccines remains a global health priority. Currently, the most advanced vaccine, known as RTS,S, has only shown modest efficacy in clinical trials. Thus, the development of more efficacious vaccines by improving the formulation of RTS,S for increased efficacy or to interrupt malaria transmission are urgently needed. The RTS,S vaccine is based on the presentation of a fragment of the sporozoite antigen on the surface of virus-like particles (VLPs) based on human hepatitis B virus (HBV). In this study, we have developed and evaluated a novel VLP platform based on duck HBV (known as Metavax) for malaria vaccine development. This platform can incorporate large and complex proteins into VLPs and is produced in a Hansenula cell line compatible with cGMP vaccine production. Here, we have established the expression of leading P. falciparum malaria vaccine candidates as VLPs. This includes Pfs230 and Pfs25, which are candidate transmission-blocking vaccine antigens. We demonstrated that the VLPs effectively induce antibodies to malaria vaccine candidates with minimal induction of antibodies to the duck-HBV scaffold antigen. Antibodies to Pfs230 also recognised native protein on the surface of gametocytes, and antibodies to both Pfs230 and Pfs25 demonstrated transmission-reducing activity in standard membrane feeding assays. These results establish the potential utility of this VLP platform for malaria vaccines, which may be suitable for the development of multi-component vaccines that achieve high vaccine efficacy and transmission-blocking immunity.